Influence of incorporation of fluoroalkyl methacrylates on roughness and flexural strength of a denture base acrylic resin - Tatiana Ramirez Cunha; Romulo Rocha Regis; Marília Rodrigues Bonatti; Raphael Freitas de Souza (University of São Paulo, 2009)
Fluorinated denture base acrylic resins can present more stable physical properties when compared with conventional polymers. This study evaluated the incorporation of a fluoroalkyl methacrylate (FMA) mixture in a denture base material and its effect on roughness and flexural strength. A swelling behavior assessment of acrylic resin specimens (n=3, per substance) after 12 h of FMA or methyl methacrylate (MMA) immersion was conducted to determine the solvent properties. Rectangular specimens (n=30) were allocated to three groups, according to the concentration of FMA substituted into the monomer component of a heat-polymerized acrylic resin (Lucitone 550), as follows: 0% (control), 10% and 20% (v/v). Acrylic resin mixed with concentrations of 25% or more did not reach the dough stage and was not viable. The surface roughness and flexural strength of the specimens were tested. Variables were analyzed by ANOVA and Tukey's test (a=0.05). Immersion in FMA produced negligible swelling, and MMA produced obvious swelling and dissolution of the specimens. Surface roughness at concentrations of 0%, 10% and 20% were: 0.25 ± 0.04, 0.24 ± 0.04, 0.22 ± 0.03 mm (F=1.78; p=0.189, not significant). Significant differences were found for flexural strength (F=15.92; p<0.001) and modulus of elasticity (F=7.67; p=0.002), with the following results: 96 ± 6, 82 ± 5, 84 ± 6 MPa, and 2,717 ± 79, 2,558 ± 128, 2574 ± 87 MPa, respectively. The solvent properties of FMA against acrylic resin are weak, which would explain why concentrations over 20% were not viable. Surface changes were not detected after the incorporation of FMA in the denture base acrylic resin tested. The addition of FMA into denture base resin may lower the flexural strength and modulus of elasticity, regardless of the tested concentration.